Power, politics, and rural development : essays on India - Lieten, G K 1946- (New Delhi : Manohar, 2003)
With reference to Panchayats in India.
Includes bibliographical references (p. [261]-276) and index.
Keywords: Local government -- India; Rural development projects -- India; India -- Rural conditions